PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PENJUALAN KOMPUTER DAN ACCESSORIES PADA TOKO MUJAHIDAH COMPUTER BERBASIS WEB - Rahmi Sartika Fitri; Kasman Rukun; Nurindah Dwiyani (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
The development of information and communication technologies now provides new opportunities for businesses to increase revenue and expand the marketing area. Example is the use of e-commerce. The implementation of e-commerce is one good way to deal with the existing trade competition. So the marketing information system design is a solution for Mujahidah Computer to overcome marketing problems. The system design is described in three stages diagram of Unified Modeling Language (UML). These stages are context diagram, use case diagrams, and activity diagrams. This system uses PHP programming language with Codeigniter framework and MySQL as the database. This information system will be facilitated with online sales to expand the marketing targets and provides information about the Mujahidah Computer a means of promotion. This system will also provide the comment form so that users can provide a response to the system.Keywords: Information System, E-commerce, Codeigniter